smasons2001
smasons2001
02-11-2021
Mathematics
contestada
-3(y - 1) + 8(y - 3) = 6y + 7 - 5y
Respuesta :
yutrferftghr
yutrferftghr
02-11-2021
Answer:
y=1
Step-by-step explanation:
-3y+3+8y-24=6y+7-5y
5y+3=7+y
4y=4
y=1
Answer Link
VER TODAS LAS RESPUESTAS ( 88+ )
Otras preguntas
PLEASE HELP Explain how the algebraic properties are applied in the steps to solving equations and use them to solve 1/2x+4=12. 10 points
Which will result in a perfect square trinomial? a.(3x – 5)(3x – 5) b.(3x – 5)(5 – 3x) c.(3x – 5)(3x 5) d.(3x – 5)(–3x – 5)?
what do I do first? do I multiply 11×11.091 first?
A national retail chain has asked Susan to conduct a customer satisfaction analysis. How should Susan collect the data? A. by conducting a census of the
Ignoring personal feelings in the workplace is a big mistake?
The stable platform has developed from a series of _____.
Which of the following is a graph of y = 1/2 x^2?
If f(x) = 2x2 1, what is f(x) when x = 3? a 1 b 7 c 13 d 19 9 of 50
if 6 banannas are $1.50 and 5 oranges are $3.00 how much would it cost if i buy 2 banannas,and 2 oranges.
Which executive branch agencies best represent the principles in the United Nations Declaration of Human Rights and have solid accomplishments that support the